Islands of rage & hope - Ringo, John, 1963- (Ringo, John, 1963- Black tide rising., 2014)
"With the world consumed by a devastating plague, what was once a band of desperate survivors bobbing on the Atlantic ocean has now become Wolf Squadron, the only hope for the salvation of the human race. Banding together the remains of the US Navy, Wolf Squadron, and its leader Steve Smith, plans to retake the mainland from the infected, starting with North America. The next step: produce a vaccine. But to do that, forces led by Smith's terrifyingly precocious daughters Sophia and Faith must venture into a sea of infected to obtain and secure the needed materials"--